Multistakeholder platforms for natural resource governance: Lessons from eight landscape-level cases - Ratner, B.D.; Larson, A.M.; Sarmiento Barletti, J.; ElDidi, Hagar; Catacutan, D.; Flintan, Fiona E.; Suhardiman, D.; Falk, Thomas; Meinzen-Dick, Ruth S. (Resilience Alliance, Inc., 2022)
Multistakeholder platforms (MSPs) are the subject of increasing attention and investment in the domain of collaborative natural resource governance, yet evidence-based guidance is slim on policy and investment priorities to leverage the MSP approach. We provide a comparative analysis of eight landscape-level MSPs spanning seven countries (Peru, Brazil, India, Tanzania, Ethiopia, and a cross-border case from Kenya and Somalia), representing a diversity of resource systems covering forests, rangelands, and multiuse agricultural landscapes. Applying an adapted social-ecological systems framework, our synthesis identifies the influence of these MSPs on patterns of stakeholder interaction and draws implications for the design and organization of MSPs that are both appropriate and effective. From the cases, we distill lessons addressing: (1) how to design an MSP in relation to the governance context, including the fit between institutional and ecological dimensions of the system and with attention to cross-scale linkages; (2) how to implement inclusive processes that address power inequities, including through capacity building and procedural rules; and (3) how to support adaptive learning to expand the MSP’s influence over time, including monitoring outcomes, adapting the scope of stakeholder engagement, and investing in MSP durability.